Sistem Informasi Persediaan Barang Berbasis Web Menggunakan Metode Agile Pada Pt. Mitra Dinamika Utama - Akbar, Dimas; Pramudito, Dendy K; Edora, Edora (Jurnal Pelita Teknologi, 2024)
As information technology develops today, the use of computers has become a very good alternative way for information needs and is the right solution for managing data compared to information carried out manually. However PT. Mitra Dinamika Utama still uses manual recording of goods, which results in problems such as recording warehouse stock which still uses traditional methods such as recording the incoming and outgoing goods using a notebook, making it easy for errors to occur when managing goods data. The method used in this research is the Agile Development (scrum) method, and will be built using the PHP programming language and MySQL database. The aim of this research is to create a website- based inventory information system that will help companies increase the efficiency of recording warehouse stock. The results of this research show that PT. Mitra Dinamika Utama can manage warehouse stock more effectively and efficiently, because the recording process becomes smoother and integrated with other business processes. This enables faster access to data, better decision making, and increased overall productivity.